PENGARUH KETERBUKAAN KOMUNIKASI PIMPINAN PERUSAHAAN DALAM MEMBENTUK PENINGKATAN DAN KENYAMANAN KINERJA KARYAWAN DI PT .GLOBAL SINERGI KARTU - Amin Sadiqin; Ulfa Maslakhatul Khasanah (LP2M Universitas Bina Bangsa, 2021)
Openness of communication is one part of the science of business ethics, a business science that is believed to provide benefits not only to companies or business people, but also to employees, the general public, and the environment. Openness of communication becomes a principle in running a company in which there are many diverse people. Open communication will have an impact on mutual trust with each other. Open communication will then transform into effective communication. Effective delivery of information will automatically launch a workflow in a company so that it gets maximum results. PT. Global Synergy Karut is one of the companies that run this rule. Employees of the company stated that they tended to like the communication openness policy implemented by their leadership. Employees feel given freedom of speech and get clear and definite information. Research with this type of qualitative research, as well as using in-depth interview methods to obtain data, shows the results that the application of the principle of information openness has a real positive impact on employee performance.